The future of warm-season, tropical and subtropical forage legumes in sustainable pastures and rangelands - Muir, James P; Pitman, William D; Dubeux, Jose C; Foster, Jamie L (African journal of range & forage science, 2014)
Forage legumes have the potential to contribute substantially to warm-season, subtropical and tropical pastures and rangelands. Compared to grasses, they have advantages in accessing subsoil nutrients and moisture; legumes typically concentrate protein in forage, even in infertile soils, and they can also provide ruminants with plant proteins and soluble carbohydrates that increase digestibility of grasses when consumed in legume-grass mixtures. Yet their inclusion in warm-season, subtropical or tropical pasture seed mixes or rangeland rehabilitation is minimal considering the percentage of grasslands coverage in these regions. Why have past diligent attempts failed to develop the germplasm, agronomic techniques, dissemination and ultimate widespread acceptance by land managers in regions where these legumes are widely adapted? Successful forage legume reports indicate that farmers' participation in technology development, persistence with minimal management, adequate seed supply following release of new varieties, meeting recognised needs, delivery of clear benefits and profits, and communication among researchers, extension and stakeholders are crucial. Current and future research and development programs based on limited past successes and widespread failures should enhance successful commercial use of warm-season, subtropical and tropical forage legumes.